2020
DOI: 10.1073/pnas.2002630117
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal role of the transcriptional co-activator YAP in trophoblast stemness of the developing human placenta

Abstract: Various pregnancy complications, such as severe forms of preeclampsia or intrauterine growth restriction, are thought to arise from failures in the differentiation of human placental trophoblasts. Progenitors of the latter either develop into invasive extravillous trophoblasts, remodeling the uterine vasculature, or fuse into multinuclear syncytiotrophoblasts transporting oxygen and nutrients to the growing fetus. However, key regulatory factors controlling trophoblast self-renewal and differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 59 publications
19
100
0
Order By: Relevance
“…The comprehensive analysis of the results suggests that YAP/TAZ and downstream self-renewal-associated genes are involved in the biological process of radial shockwave-mediated promotion of SCB-SPC self-renewal. The results are consistent with previous studies that demonstrated that YAP correlated closely with the self-renewal of ES cells because elevated YAP maintains the potency of ES cells [ 46 , 47 ]. Meanwhile, others reported that YAP/TAZ are dispensable for ES cell fate [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…The comprehensive analysis of the results suggests that YAP/TAZ and downstream self-renewal-associated genes are involved in the biological process of radial shockwave-mediated promotion of SCB-SPC self-renewal. The results are consistent with previous studies that demonstrated that YAP correlated closely with the self-renewal of ES cells because elevated YAP maintains the potency of ES cells [ 46 , 47 ]. Meanwhile, others reported that YAP/TAZ are dispensable for ES cell fate [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…Like in the mouse, YAP is essential for the development of the human TE and placenta, and its expression is negatively correlated with pregnancy disorders like preeclampsia [40,41]. The YAP-TEAD4 transcriptional program was recently shown to maintain human trophoblast stemness in primary cytotrophoblasts and repress cell fusion [40].…”
Section: Yap In the Human Vs The Mouse Embryo And Placentamentioning
confidence: 99%
“…Interestingly, YAP1 is expressed in the human placenta and its levels are downregulated in patients with preeclampsia ( Sun et al , 2018 ), indicating that Hippo signaling may be important for human trophoblast lineage development. In support of this notion, a recent study using human cell models revealed that YAP1 and TEAD4 promote self-renewal of cytotrophoblast progenitor cells, while inhibiting formation of differentiated syncytiotrophoblast cells ( Meinhardt et al , 2020 ). Based on the function of the Hippo signaling pathway in mouse preimplantation embryos and embryos from other large animal species such as cattle and pigs ( Negron-Perez and Hansen, 2018 ; Cao et al , 2019 ; Emura et al , 2020 ; Sharma and Madan, 2020 ), it is easy to postulate that Hippo signaling plays a fundamental role in human preimplantation embryo development and early lineage formation.…”
Section: Discussionmentioning
confidence: 87%